Social games as partial platforms for identity co-creation - Willson, Michele (University of Queensland, School of Journalism and Communication, 2015)
While social games such as Zynga’s FarmVille are often positioned as poor gaming experiences or as disguised financial and data extraction processes (Bogost, 2010; Rossi, 2009), this paper considers social games instead as part of a wider regime of social interaction and creative identity work. Social games, by definition, are located within extensive online social networks. Gameplay is thus situated within a number of overlapping contexts: the game, the broader social network, the material conditions of access, including different devices (mobile or desktop) and different locations. Moreover, given widely discussed differences between social game players and console and PC-based game players (Wohn, 2011: 199), and game play mechanics, these broader contexts further a reading of social gameplay as part of the diverse milieu of everyday life. This paper argues social games are spaces of creative expression, social dynamics and identity co-creation that cannot be understood without their broader contexts.